Growing and study of optical and luminescence properties of scintillation oxide crystals - Nagornaya, L.L.; Bondar, V.G.; Vostretsov, Yu.Ya.; Grinyov, B.V.; Katrunov, K.A.; Martynov, V.P.; Pirogov, E.N.; Starzhinsky, N.G.; Tupitsyna, I.A. (Functional Materials, 2005)
Discussed are the peculiarities of the oxide crystal growing by Czochralski technique, the effects of the growth atmosphere on the structure transformation extent and direction, stoichiometric disordering of the oxide melts, the various defect formation nature in the crystals. It is just the redox potential of the growth atmosphere defining the oxygen thermochemical activity in the oxide melts that has been shown to influence considerably the extent and direction of the processes mentioned. The resulting effect of factors influencing the internal structure has been found to define the coordination of clusters of the crystal-forming components and the melt ability of single-phase crystallization.